A Comprehensive Review of the Potential Use of Green Tea Polyphenols in the Management of COVID-19. (3rd December 2021) - Tallei, Trina Ekawati; Fatimawali; Niode, Nurdjannah Jane; Idroes, Rinaldi; Zidan, B. M. Redwan Matin; Mitra, Saikat; Celik, Ismail; Nainu, Firzan; Ağagündüz, Duygu; Emran, Talha Bin; Capasso, Raffaele
Abstract : Green tea is produced from Camellia sinensis (L.) buds and leaves that have not gone through the oxidation and withering processes used to produce black and oolong teas. It was originated in China, but its cultivation and production have expanded to other Eastern Asian countries. Several polyphenolic compounds, including flavandiols, flavonols, flavonoids, and phenolic acids, are found in green tea and may constitute greater than 30% of the dry weight. Flavonols, especially catechins, represent the majority of green tea polyphenols. Green tea polyphenolic compounds have been reported to confer several health benefits. This review describes the potential use of green tea polyphenols in the management of coronavirus disease 2019 (COVID-19). The immunomodulatory, antibacterial, antioxidant, and anti-inflammatory effects of green tea polyphenols have also been considered in this review. In addition to describing the bioactivities associated with green tea polyphenols, this review discusses the potential delivery of these biomolecules using a nanoparticle drug delivery system. Moreover, the bioavailability and toxicity of green tea polyphenols are also evaluated.